Relationship between climate and geographical variation of local woody species richness within the Mediterranean-type region of Chile. Issue 1 (December 2016) - Becerra, Pablo
Abstract Background Latitudinal and altitudinal patterns of plant species richness have frequently been related to different climate variables such as precipitation, temperature and evapotranspiration. However, studies assessing this relationship have mostly compared different regions and used regional scales of richness (in quadrants of several km2 ). It is less known the relationship between climate and geographical patterns of species richness in local scales (richness in < 1 ha plots). For central Chile some studies have described geographical patterns of plant species richness, but only using regional scales to quantify richness. It is not known how local richness of plant species varies geographically and if climate variables are related to this variation. In this paper I evaluated latitudinal and altitudinal trends of local richness of woody species within forest ecosystems of the Mediterranean-type climate region in central Chile, and explored if these patterns are related to climatic variables. We used data collected in the field as well as published data of composition of woody species in plots of 100 m2 collected in different localities within this region. Climatic variables were obtained for each locality from isoclimate curves published for the whole region. Results Local woody species richness was positively related to latitude and negatively related to elevation. Also, it was positively related to annual precipitation and atmospheric relative moisture, and negatively to mean minimal temperature of winter. In addition, precipitation increased with latitude, and minimal temperature of winter decreased with elevation. Conclusion These results suggest that climate may be an important driver of altitudinal and latitudinal patterns of local species richness of woody species in central Chile.